The experience of older adults who participate in a bibliotherapy/poetry group in an older adult inpatient mental health assessment and treatment ward. Issue 4 (2nd October 2019) - Chamberlain, David
ABSTRACT: Bibliotherapy has developed from prescribed self-help books from a clinician to groups where a selection of poetry is read aloud. There is little research on the benefit of a reading group on an older adult psychiatric ward. This research aims to identify the experiences of participants in a reading group, investigating the value of reading aloud. Ten 1 hour groups were run on a psychiatric ward. Using phenomenographic methods participants were interviewed and the transcripts analysed. There were 39 attendances with 15 different people attending. Of the 15 people who attended 4 consented to take part in the research. Of those interviewed experiences emerged of empathy, confidence, and identity. Reading aloud increased confidence and a sense of self-identity. Using themes, topics could be discussed and feelings and emotions articulated in a safe and supportive environment. However further research is suggested before Bibliotherapy is recommended as part of routine clinical practice.